Construction and application of a new index for root architecture quantification in arid and semi-arid regions - Li, Qiang; Ai, Feng; Kang, Furen; Zhang, Zheng; Tuo, Dengfeng (Frontiers in Environmental Science, 2023)
During the restoration of degraded vegetation, the mutual matching of underground root systems is crucial for the formation and effective function of the future plant community. In this study, the Amoeba graphic method was integrated to comprehensively establish a root framework index (RFI), based on the three dimensions of root morphology, as well as quantitative and spatial connection characteristics, to quantify the root system architecture. The root development characteristics of alfalfa (T-type), switchgrass (F-type), and mixed planting with alfalfa and switchgrass (T+F type) were monitored at the test positions. The RFI parameters comprise the acting coefficient of the root framework, root density, root framework degree, and soil bulk density. The RFI values of T-, F-, and T+F-type were 0.38, 0.86, and 1.68, respectively, and were found to provide a well representation of the root structure characteristics. The findings obtained in this study provide scientific support for the ecological construction and evaluation of degraded vegetation.